Impact of positive resection margins (R1) on long-term survival of patients with advanced diffuse type gastric cancer. (1st June 2022) - Gaspar-Figueiredo, S; Joliat, G-R; Borgstein, A B J; Van Berge Henegouwen, M I; Brunel, C; Demartines, N; Allemann, P; Schäfer, M
Abstract: Objective: Gastric cancer (GC) is a leading cause of cancer-related mortality worldwide. Diffuse type GC have a much worse prognosis compared to intestinal type GC. There is an ongoing debate whether microscopic involvement of the proximal margin (R1 resection) influences overall survival (OS) in advanced gastric cancer. The aim of this study was to assess OS in patients with diffuse gastric cancers and positive lymph node involvement who underwent oncological gastrectomy with R0 and R1 resections. Methods: All consecutive patients from two tertiary centers operated with curative intent for diffuse gastric cancer between January 2005 and December 2018 were analyzed. Patients with R2 resections or missing data were excluded. Extracted data included demographics, major comorbidities, ASA score, neo-adjuvant treatment, pre- and postoperative staging (TNM 8th edition), postoperative complication with grading according to Clavien classification, survival data and pattern of recurrence. Lymph node involvement was based on pathology. Kaplan-Meier curves with log-rank test for comparison were used to evaluate survival between groups. Results: A total of 94 patients with diffuse gastric cancer were included. Two patients were excluded because of R2 resection and missing data regarding pathology, leaving a cohort of 92 patients (48 male, 44 female, median age 62 years). Sixty-four patients were lymph node positive (pN+); 48 patients (75%) with R0 resection and 16 patients (25%) with R1 resection. No difference in terms of preoperative data and intraoperative characteristics was found between R0 and R1 groups. Median OS was better in the R0 group (27 months, 95% CI 17–37) compared to R1 group (7 months, 95% CI 3–11, p<0.001). Similar results were found with disease-free survival (DSF) (25 vs. 6 months, p=0.002). On multivariable analysis, T stage and resection margin (R status) were independent factors predicting OS (T stage: HR 4.5, p<0.001, R status: HR 4.2, p<0.001) and DFS (T stage: HR 2.9, p=0.004, R status: HR 3.5, p=0.001) in the cohort of patients with lymph node involvement. Conclusion: The present series confirmed that patients with negative surgical margins have better OS compared to patients with positive margins in case of locally advanced diffuse GC. Therefore, R0 resections should be the goal of oncological gastrectomies.